P-128 Fecal Microbial Transplantation Shows Efficacy in Children With Refractory Ulcerative Colitis - Early Results of Phase I Clinical Trial - Kunde, Sachin; Cloney, Deborah; Conrad, Harold; Kugathasan, Subra (Inflammatory bowel diseases, 2012)
Fecal microbial transplantation (FMT) is being investigated as a promising alternative treatment option for ulcerative colitis (UC). The interest and enthusiasm is very high among patients with IBD despite lack of prospective data. Interest in FMT has largely been driven by new research into the gut microbiota, which is being appreciated as a microbial human organ with important roles in immunity and energy metabolism. We hypothesize that FMT may restore ‘abnormal’ microbiota to ‘normal’ in UC thus induce remission in refractory UC. We have initiated the first phase I clinical trial for use of FMT in UC with goals of assessing 1) the safety and tolerability, and 2) evaluate clinical response to FMT.MethodsStudy was approved by Spectrum Health institutional review board. We obtained investigational new drug (IND) approval from the U.S. FDA for use of human stool as a biologic. We plan to enroll ten children (age 7-21 yrs) with mild to moderate, treatment resistant UC. After extensive donor screening guided by FDA and American Blood Bank Association, every subject received freshly prepared 8 oz fecal enemas for 5 days over 1 week period. Pediatric ulcerative colitis activity index (PUCAI) was collected at baseline and weekly for a month after FMT. Safety data was collected using ‘common terminology criteria for adverse events v3.0’ and using FDA guidance for industry from ‘toxicity grading scale for healthy adult and adolescent volunteers enrolled in preventive vaccine clinical trials, 2007’. Clinical response was defined as a decrease in PUCAI by 15 points at one month after FMT.Figure.ResultsWe plan to enroll 10 subjects. Eight subjects have been enrolled to date and complete data is available on 3 subjects who have completed the study. Their baseline PUCAI scores were 30, 35 and 50, which improved to 15, 0 and 40 respectively, at one month after FMT. All the subjects tolerated fecal enemas without leakage. One subject received only 6 oz enemas due to feeling of fullness. No serious adverse events were noted. Symptoms associated with FMT were mild (cramping, fullness, flatulence, bloating, diarrhea and nausea, which did not need treatment) to moderate (fever in one, which responded to antipyretic and anti-histaminic medications). These symptoms were self-limiting and lasted only for the duration of FMT treatment days.Conclusion(s)Fecal microbial transplantation as an enema is feasible, well tolerated and can be performed easily in children with UC with minimal training and support. Two of three subjects achieved clinical response by reduction in PUCAI of 15 points or more. One of them had complete resolution of disease activity. More data is anticipated for the Advances in IBD meeting in December. Larger prospective and controlled studies are needed to study clinical efficacy, endoscopic healing and the mechanism of action of FMT.